Cost-effectiveness analysis of cinacalcet for haemodialysis patients with moderate-to-severe secondary hyperparathyroidism in China: evaluation based on the EVOLVE trial - Bin Wu; Lin Liu; Xiaoyang Lu; Dongsheng Hong; Kuifen Ma (BMJ Open)
Objective As the cost-effectiveness evaluation of cinacalcet and conventional therapy in China has not been reported, the objective of this study was to make a pharmacoeconomic evaluation of cinacalcet specific to the Chinese healthcare setting in patients with moderate-to-severe secondary hyperparathyroidism (SHPT) undergoing dialysis.Designs Data from Evaluation of Cinacalcet Therapy to Lower Cardiovascular Events trial were used for this analysis. A semi-Markov model was constructed to estimate quality-adjusted life years (QALYs) and lifetime costs in cinacalcet plus conventional therapy (cinacalcet strategy) compared with conventional therapy (standard strategy), in patients with moderate-to-severe SHPT undergoing dialysis. Treatment effect estimates from the unadjusted intent-to-treat (ITT) analysis and covariate-adjusted ITT analysis were used as the main analyses. Model sensitivity to variations in individual inputs and overall decision uncertainty were assessed through probabilistic sensitivity analyses.Primary and secondary outcome measures Incremental cost-effectiveness ratio (ICER) as measured by cost per QALY gained.Results The ICER for cinacalcet strategy was US$44 400 per QALY gained using the covariate-adjusted ITT analysis. Probabilistic sensitivity analysis suggested a 46.2% chance of the ICER being below a willingness-to-pay threshold of US$26 508. Treatment effects from unadjusted ITT analysis yielded an ICER of US$87 210 per QALY. The model was most sensitive to the treatment effect on mortality.Conclusions Existing evidence does not support the cost-effectiveness of cinacalcet strategy in patients with moderate-to-severe SHPT undergoing dialysis when applying a willingness-to-pay threshold of US$26 508 per QALY, whether it is using the treatment effect from covariate-adjusted ITT analysis or unadjusted ITT analysis.